Erlotinib and bevacizumab in patients with advanced non-small-cell lung cancer and activating EGFR mutations (BELIEF): an international, multicentre, single-arm, phase 2 trial - Rosell, Rafael; Thomas, Michael (The lancet. Respiratory medicine, 2017)
Summary: The tyrosine kinase inhibitor erlotinib improves the outcomes of patients with advanced non-small-cell lung carcinoma (NSCLC) harbouring epidermal growth factor receptor (EGFR) mutations. The coexistence of the T790M resistance mutation with another EGFR mutation in treatment-naive patients has been associated with a shorter progression-free survival to EGFR inhibition than in the absence of the T790M mutation. To test this hypothesis clinically, we developed a proof-of-concept study, in which patients with EGFR-mutant NSCLC were treated with the combination of erlotinib and bevacizumab, stratified by the presence of the pretreatment T790M mutation.